Viral and atypical respiratory co‐infections in COVID‐19: a systematic review and meta‐analysis. Issue 4 (19th June 2020) - Davis, Bennett; Rothrock, Ava N.; Swetland, Sarah; Andris, Halle; Davis, Phil; Rothrock, Steven G.
Abstract: Objectives: Respiratory co‐infections have the potential to affect the diagnosis and treatment of COVID‐19 patients. This meta‐analysis was performed to analyze the prevalence of respiratory pathogens (viruses and atypical bacteria) in COVID‐19 patients. Methods: This review was consistent with Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA). Searched databases included: PubMed, EMBASE, Web of Science, Google Scholar, and grey literature. Studies with a series of SARS‐CoV‐2‐positive patients with additional respiratory pathogen testing were included. Independently, 2 authors extracted data and assessed quality of evidence across all studies using Cochrane's Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology and within each study using the Newcastle Ottawa scale. Data extraction and quality assessment disagreements were settled by a third author. Pooled prevalence of co‐infections was calculated using a random‐effects model with univariate meta‐regression performed to assess the effect of study subsets on heterogeneity. Publication bias was evaluated using funnel plot inspection, Begg's correlation, and Egger's test. Results: Eighteen retrospective cohorts and 1 prospective study were included. Pooling of data (1880 subjects) showed an 11.6% (95% confidence interval [CI] = 6.9–17.4, I 2 = 0.92) pooled prevalence of respiratory co‐pathogens. Studies with 100% co‐pathogen testing (1210 subjects) found a pooled prevalence of 16.8% (95% CI = 8.1–27.9, I 2 = 0.95) and studies using serum antibody tests (488 subjects) found a pooled prevalence of 26.8% (95%, CI = 7.9–51.9, I 2 = 0.97). Meta‐regression found no moderators affecting heterogeneity. Conclusion: Co‐infection with respiratory pathogens is a common and potentially important occurrence in patients with COVID‐19. Knowledge of the prevalence and type of co‐infections may have diagnostic and management implications.